2011
DOI: 10.12968/hmed.2011.72.7.391
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of necrotizing fasciitis

Abstract: Necrotizing fasciitis is a rapidly progressive, life-threatening soft tissue infection which is rapidly fatal unless diagnosed promptly and treated with immediate debridement of necrotic tissue. As early clinical suspicion is paramount to improved survival, this review aims to increase awareness of the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Hunter et al . suggest the combination of a carbapenem with clindamycin [10]. Otherwise, If cultures demonstrate sensitive Streptococcus pyogenes, there is a general agreement that a combination of penicillin G and clindamycin (high doses) is the prefered option.…”
Section: Discussionmentioning
confidence: 99%
“…Hunter et al . suggest the combination of a carbapenem with clindamycin [10]. Otherwise, If cultures demonstrate sensitive Streptococcus pyogenes, there is a general agreement that a combination of penicillin G and clindamycin (high doses) is the prefered option.…”
Section: Discussionmentioning
confidence: 99%
“…Prompt diagnosis is imperative as necrotizing fasciitis is a surgical emergency. 5,26 In the United States, 500 to 1500 cases of necrotizing fasciitis occur each year. 27 Risk factors for necrotizing fasciitis include diabetes, peripheral vascular disease, malignancy, obesity, cirrhosis, renal failure, injection drug use, chronic corticosteroid therapy, alcohol abuse, malnutrition, and iatrogenic immunosuppression.…”
Section: Necrotizing Fasciitismentioning
confidence: 99%
“…27 Risk factors for necrotizing fasciitis include diabetes, peripheral vascular disease, malignancy, obesity, cirrhosis, renal failure, injection drug use, chronic corticosteroid therapy, alcohol abuse, malnutrition, and iatrogenic immunosuppression. 26,28 Necrotizing fasciitis may be polymicrobial or monomicrobial. Polymicrobial infection, also referred to as type I, is often due to multiple bacteria that originate from the bowel flora, typically including a mix of anaerobic and aerobic organisms.…”
Section: Necrotizing Fasciitismentioning
confidence: 99%
See 1 more Smart Citation
“…One research suggested that there were 18.1% NF inpatients with HAI [9]. Early diagnosis and rapid treatment can help prevent and reduce poor prognosis [10]; nevertheless, the diagnosis of NF is very difficult [11]. The initial signs and symptoms are often nonspecific until the patient rapidly deteriorates, and NF is commonly accompanied by shock and decreased level of consciousness [12].…”
Section: Introductionmentioning
confidence: 99%